Pengaruh Pasta Tomat Terhadap Kolesterol Darah Mencit - Nugraheni, Febriani Sarwendah Asri; Jailani, Jailani; Purwati, Sri (Bioeksperimen: Jurnal Penelitian Biologi, 2019)
This study aims to determine the effect of tomato paste on blood cholesterol in mice. It was an experimental study using a complete randomized study design consisting of four treatments P0, P1, P2, and P3 by giving tomato paste solution in a concentration of 0%, 20%, 40% and 80% and 6 replications. Data were analyzed using Anova one path and continued with BNT with a confidence level of 95%. The results showed that the tomato paste solution affected the blood cholesterol of mice due to Fhit (3.27)> F tab (3.10) and the treatment that gave the greatest effect was on giving the concentration of tomato paste solution by 80%.